THE MEANING OF LIGHT IN NIKOLA MILOSEVIC'S ARTISTIC PROSE (Živi jezici: Journal for Foreign Languages and Literatures, 2019)
In this article, the author presents the results he obtained while researching the artistic prose of Nikola Milošević - a famous Serbian philosopher and literary theorist. Contrary to the established term trilogy (it is the number of novels by the mentioned author), which was adopted by all scholars of his prose, the author of the article always insists on the term tetralogy, since he also analyzed his first novel Deus abconditus. Starting from one sentence by Samuel Beckett, the author of the article focused not only on the mysterious meaning of light - a phenomenon unnoticed in the literary work of Nikola Milosevic, but also on the dynamic relationship between two opposing hints (melancholic and metaphysical) that radiate from his unusual prose.
Keywords: artistic prose; hidden God; light; meaning,; melancholy tendency; metaphysical tendency; tetralogy